2021
DOI: 10.1523/jneurosci.2459-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Reliability Automatically Biases Temporal Integration of Discrete Perceptual Targets in the Human Brain

Abstract: Many decisions, from crossing a busy street to choosing a profession, require integration of discrete sensory events. Previous studies have shown that integrative decision-making favors more reliable stimuli, mimicking statistically optimal integration. It remains unclear, however, whether reliability biases operate even when they lead to suboptimal performance. To address this issue, we asked human observers to reproduce the average motion direction of two suprathreshold coherent motion signals presented succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 51 publications
6
21
2
Order By: Relevance
“…Direction-specific responses started at about .2 s after motion onset and remained strong for the duration of the epoch. The onset time is comparably late 44 for the directionspecific activity to reflect early, sensory responses (e.g., C1/P1), while it closely matches other well-documented correlates of decision-making such as the central-parietal positivity (i.e., CPP) [3][4][5]29,30 . Interestingly, tuning to the derived, average motion direction -which was never actually presented in the displays -was stronger than tuning to either of the two component motion stimuli displayed in the left and right hemifields.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Direction-specific responses started at about .2 s after motion onset and remained strong for the duration of the epoch. The onset time is comparably late 44 for the directionspecific activity to reflect early, sensory responses (e.g., C1/P1), while it closely matches other well-documented correlates of decision-making such as the central-parietal positivity (i.e., CPP) [3][4][5]29,30 . Interestingly, tuning to the derived, average motion direction -which was never actually presented in the displays -was stronger than tuning to either of the two component motion stimuli displayed in the left and right hemifields.…”
Section: Resultssupporting
confidence: 71%
“…Continuous EEG data were pre-processed offline using the FASTER 38 pipeline and segmented into 1 s epochs, time-locked to the onset of coherent motion. We chose to measure neural responses using EEG because this method affords millisecond-level temporal resolution, and because we and others have shown that timeresolved direction-selective responses to brief dot-motion stimuli can be reliably decoded from EEG recordings using multivariate decoding [3][4][5]39,40 (Figure 2A EEG analyses. For each trial (i.e., test), the EEG epoch was compared with the average (i.e., the ERP) of other, training trials using multivariate Mahalanobis distance 41 ("-" symbol).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations